International Aspect of Legal Regulation of Corruption Offences Commission on the Example of Law Enforcement Agencies and Banking System of Ukraine - REZNIK, Oleg M.; KLOCHKO, Alyona M.; PAKHOMOV, Vladimir V.; KOSYTSIA, Olga O. (Journal of Advanced Research in Law and Economics, 2017)
The article analyzes the legislation such countries as Ukraine, the Russian Federation (hereafter – RF) and the Republic of Belarus, norms of which provide a system of measures to combat corruption as well as responsibility for such kind of offences. Moreover the article considers such burning question as counteraction of such kinds of offences and also different legislative approaches on the definition of ‘corruption’ in the countries mentioned above. We consider the criminal-legal norms as provided in the Criminal Code of Ukraine, establishing the responsibility for obtaining of unlawful benefit by the officials. We study the provisions of the current legislation of Ukraine aimed at prevention of corruption in the society. The special attention is given to the concepts of ‘illegal benefit’ and ‘bribe’, the key differences of these terms are defined. Also an attention is paid to the terms ‘officials’ and ‘law enforcement officials’. This article also discusses some features of committing crimes by the officials of the banking institutions. It is noted that the committing of such crimes is the problem promoting the destabilization of the banking system. The underlying mechanisms and the high latency of these crimes, being made mostly by organized criminal groups, entail negative consequences for the economy of each individual country and in general all over the world. It should also be noted that the basic principles and methods of dealing with corruption offences were identified in the work as well as a vector of legal regulation of every particular state in the defined area which is the basis of their anti-corruption policy. Furthermore comparative analysis of the administrative and criminal offences, which relate to corruption in RF, Ukraine and Belarus, was carried out. As a result of carrying out the analysis it became obvious that availability of uniform system of corruption offences classification for RF, Ukraine and Belarus is not significant and the legislation of each of the investigated countries provides differentiated approaches in understanding this question. Also we shall note, that not each of the designated states makes exhaustive list of offences that refer to corruption that undoubtedly complicates studying an actual condition of corruption in the country.  A great share of attention in the article was paid to the studying of types and volumes of penalties for corruption acts. It was conducted a comparative characteristics of species and rigidity of penalty for corruption offences. As a conclusion of the study common and distinctive features of the anti-corruption legislation in Ukraine, RF and Belarus were highlighted. The conclusions are made that researched issues not lose its relevance because of periodic committing of corruption offences by the officials of law enforcement agencies and banking institutions.